“Es tu pared, pero era mi niña”: Activist discourses on graffiti in the linguistic landscape of Cancún, Quintana Roo (Mexico) - Harjus, Jannis (2025)
This article deals with the linguistic analysis of graffiti in public spaces in Cancun, Quintana Roo, Mexico, in order to clarify the role of activist discourses present in graffiti in the dynamics of “reterritorialization” of a specific urban space. The data examined here comes from messages in Cancun’s downtown after the protests of March 8, 2024, and are therefore socially critical discourses at the local, regional, national, and global levels were to be expected. Just after the protest marches, on the walls and floors around Cancún City Hall, a total of 181 graffiti messages were photographed and categorized using the MAXQDA program. The discourse-linguistic analysis based on qualitatively analyzed data of the corpus shows that various activist discourses intertwine as “interdiscourses” that co-create and reterritorialize urban space, and deal especially with violence against women and children in Mexico.